Modeling, Vector Control and Simulation of Wind Turbine with Dual Excited Synchronous Generator - أبوطبق, نسمت (Latakia University Journal -Engineering Sciences Series, 2020)
This paper deals with a new excitation control technology for the synchronous generator with two excitation windings, it is vector control by flux orientation. The main goal is to control the angle of the load to make the generator more stable and more freedom to magnetic flux than to be placed on the axis of the pole. The paper includes proportional additional control that improves the transient state response of the mechanical velocity. Benefit of the Park transformations for the model of the synchronous generator to develop a vector control algorithm by integral proportional controllers. The simulation results in MATLAB showed good performance of the proposed control system for transient and steady-state conditions.